PENDAMPINGAN BELAJAR MATEMATIKA INOVATIF (JARIMATIKA) DALAM PENINGKATAN HASIL BELAJAR SISWA SEKOLAH DASAR - Lailatul Inayah; Milna Wafirah (khidmatan, 2024)
This Community Service (PkM) activity was conducted in Tempursari Hamlet to address the low learning outcomes in Mathematics among Elementary School (SD) students, particularly concerning mastery of basic arithmetic operations, exacerbated by insufficient guidance at home. The main objective of the program was to improve Mathematics learning outcomes through innovative educational mentoring. The method employed was Participatory Action Research (PAR), which involved a continuous cycle of Planning, Action, Observation, and Reflection. The core intervention implemented was the Jarimatika Method, a play-based learning model utilizing the hands and fingers as a visual and kinesthetic counting tool. The results from PAR Cycle I demonstrated that Jarimatika successfully increased basic arithmetic competence and student interest significantly, as students were able to solve problems quickly and correctly. Although challenges related to differences in student comprehension were noted, the overall findings confirm that employing the innovative Jarimatika method offers an effective solution for transforming students' perception of Mathematics and enhancing their academic achievement.